Integration of Artificial Intelligence in Islamic Religious Education: Opportunities, Challenges, and Future Projections in the Society 5.0 Era - Azzahra Maya Pramesti; Rika Nurhidayah; Imam Makruf (LP3M KH Yazid Karimullah Institute, 2026)
The development of the Society 5.0 era encourages the integration of Artificial Intelligence (AI) in Islamic Religious Education learning. Therefore, this study aims to analyze the opportunities, challenges, and projections of AI integration in Islamic Religious Education learning. This study uses a descriptive qualitative method with literature review and content analysis techniques. The results show that AI has the potential to create adaptive and personalized learning, increase motivation, encourage media innovation, and improve the effectiveness of learning evaluation. However, in the process there are challenges such as shifting value orientations, limited teacher digital literacy, the validity of religious material, ethical issues, and the risk of student dependency. Future projections indicate that AI will evolve towards data-driven adaptive learning with the role of teachers as facilitators and value directors. Thus, the use of AI in Islamic Religious Education needs to be carried out in a balanced manner between technological innovation and Islamic values.